Development under conditions of inequality and distrust: Social cohesion in Latin America - Ferroni, Marco A.; Mateo, Mercedes; Payne, Mark (International Food Policy Research Institute, 2008)
This paper analyzes the role of social cohesion in economic and institutional development and, broadly, the creation of welfare in Latin America. The paper defines the concept of social cohesion with reference to the notions of social capital and inequality. Using data and literature on Latin America, the paper argues that low interpersonal trust and entrenched inequality interfere with cohesion. The paper develops and introduces an exploratory index of cohesion structured around the definition proposed. Relying on correlations, and with appropriate caveats, the paper uses this index to explore tentative linkages between levels of cohesion and development outcomes. The paper presents evidence of positive linkages among social cohesion and economic growth, investment and innovation capacity, governmental effectiveness, the quality of public policies, and the predictability of the policy environment. Finally, the paper discusses the significance of these findings and some of the policy implications.